2023
DOI: 10.1071/hc23041
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve vaccine coverage of pregnant women in Aotearoa New Zealand

Flynn Macredie,
Esther Willing,
Pauline Dawson
et al.

Abstract: Introduction Maternal vaccination against influenza and pertussis protects mothers and babies from severe disease and is recommended and funded in Aotearoa New Zealand. Despite this, maternal vaccination uptake is low, varies by region and is inequitable, with Māori and Pacific māmā (mothers) less likely to receive vaccination. Aim To determine what interventions currently exist to support and encourage maternal vaccination against influenza and pertussis and what changes and interventions could be imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The need to address Māori (& Pacific) inequities in uptake of maternal vaccination against influenza and pertussis is addressed by Macredie and colleagues in their kaupapa Māori-aligned qualitative study. 5 They interviewed Māori and Pacific hapū mama (pregnant mothers) and found that building and maintaining trust and giving mother's time and autonomy to make a decision on being vaccinated was essential.…”
Section: Primary Health Care: Walking Backwards Into the Future?mentioning
confidence: 99%
“…The need to address Māori (& Pacific) inequities in uptake of maternal vaccination against influenza and pertussis is addressed by Macredie and colleagues in their kaupapa Māori-aligned qualitative study. 5 They interviewed Māori and Pacific hapū mama (pregnant mothers) and found that building and maintaining trust and giving mother's time and autonomy to make a decision on being vaccinated was essential.…”
Section: Primary Health Care: Walking Backwards Into the Future?mentioning
confidence: 99%